2016
DOI: 10.1038/ncomms12983
|View full text |Cite
|
Sign up to set email alerts
|

Epigenomic profiling of primary gastric adenocarcinoma reveals super-enhancer heterogeneity

Abstract: Regulatory enhancer elements in solid tumours remain poorly characterized. Here we apply micro-scale chromatin profiling to survey the distal enhancer landscape of primary gastric adenocarcinoma (GC), a leading cause of global cancer mortality. Integrating 110 epigenomic profiles from primary GCs, normal gastric tissues and cell lines, we highlight 36,973 predicted enhancers and 3,759 predicted super-enhancers respectively. Cell-line-defined super-enhancers can be subclassified by their somatic alteration stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
120
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(132 citation statements)
references
References 77 publications
(137 reference statements)
8
120
2
Order By: Relevance
“…As suggested for other cancers (Akhtar-Zaidi et al, 2012; Ooi et al, 2016), we observed enhancer variation across melanomas. Despite this heterogeneity, we find the AMIGO2 SE to be present in all melanoma cells studied and inactive in NHMs largely through the lack of BET proteins and H3K27ac.…”
Section: Discussionsupporting
confidence: 85%
“…As suggested for other cancers (Akhtar-Zaidi et al, 2012; Ooi et al, 2016), we observed enhancer variation across melanomas. Despite this heterogeneity, we find the AMIGO2 SE to be present in all melanoma cells studied and inactive in NHMs largely through the lack of BET proteins and H3K27ac.…”
Section: Discussionsupporting
confidence: 85%
“…enhancers) stratify FLC from NML samples better than transcription at proximal TREs or gene bodies, similar to previous reports (Corces et al, 2016(Corces et al, , 2018. These findings are consistent with other studies (Franco et al, 2018;Van Groningen et al, 2017;Ooi et al, 2016) that have shown enhancer activity is more sensitive than gene expression for sample classification (e.g., tumor-normal, tumor subtypes, cell types). Unlike other methods to identify enhancers, such as assay for transposaseaccessible chromatin using sequencing (ATAC-seq) or chromatin immunoprecipitation and sequencing (ChIP-seq) for enhancer-associated histone modifications or proteins, ChRO-seq identifies active regulatory elements as well as actively transcribed genes.…”
Section: Discussionsupporting
confidence: 92%
“…While the potential safety concerns associated with Wnt‐targeted therapies are legitimate, similar complications are also relevant with all drugs. If used and integrated correctly (Cancer Genome Atlas Research, ), the recent deluge of genomic (Cancer Genome Atlas Research, ), epigenomic (Ooi et al , ) and functional profiles from cancer patients (van de Wetering et al , ) will pave a clear path forward to identify the appropriate patients for a specific Wnt inhibitor.…”
Section: Resultsmentioning
confidence: 99%